WEALTH AND POWER IN THE NOVEL PRIDE AND PREJUDICE BY JANE AUSTEN - Rima Sarah (CALL, 2022)
The problem of social class becomes a unique object which would be discovered in the novel Pride and Prejudice. The study aimed to determine the influence of social class on British society and represent the reflection of social class in British society in the novel. A method used in this research was qualitative descriptive. Data that were collected were in the form of narration and dialogue in the novel Pride and Prejudice. Furthermore, this study used the Marxist concept (1995:25) to analyse the data. The findings of this research were the discovery of the impact of social class on British society in the novel Pride and Prejudice, namely Pride and Prejudice as the title in the novel and the invention of the forms of social class which can be found in the novel Pride and Prejudice, such as status, wealth, and power. Keywords: Marxist Theory, Jane Austen, Pride and Prejudice, social class